EDUKASI TATA KELOLA DAN PENYEMBELIHAN HEWAN QURBAN SECARA SYAR’I PADA KAMPUNG TEMATIK DRUM BUJANA - winanti, winanti; Basuki, Sucipto; Kamar, Karnawi; Himmy’azz, Istajib Kulla; Kumoro, Dwi Ferdiyatmoko Cahya; Adiyanto, Adiyanto; Purno, Marhaendro; Yulia, Yayah; Nurasiah, Nurasiah; Hasna, Shoftwatun; Suwita, Jaka; Jubaida, Ida; Yusuf, Yusuf (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2023)
Educational activities on the governance of the syar'i slaughter of sacrificial animals are carried out at the At-Tauhid mosque which is the location of the Bujana Drum thematic village which is the assisted village/village of the Insan Pembangunan Indonesia University. There were 12 participants in the activity consisting of lecturers, students, heads of DKM/mosque administrators and the community. The activity begins with a request, implementation of activities, and preparation of the final report by the implementing team. The objectives of the activity include educating DKM management and the community in managing and slaughtering sacrificial animals in accordance with the sunnah. Governance that must be carried out by the DKM management and the community in slaughtering and distributing the appropriate sacrificial animals so that the DKM administrators and the community both understand correctly about the management of sacrificial animals, the qurban contract and the procedures for slaughtering, distribution of qurban meat